Effect of Structure of Polymers Grafted from Graphene Oxide on the Compatibility of Particles with a Silicone-Based Environment and the Stimuli-Responsive Capabilities of Their Composites - Zygo, Monika; Mrlik, Miroslav; Ilcikova, Marketa; Hrabalikova, Martina; Osicka, Josef; Cvek, Martin; Sedlacik, Michal; Hanulikova, Barbora; Munster, Lukas; Skoda, David; Urbánek, Pavel; Pietrasik, Joanna; et al. (Nanomaterials (Basel, Switzerland), 2020)
This study reports the utilization of controlled radical polymerization as a tool for controlling the stimuli-responsive capabilities of graphene oxide (GO) based hybrid systems. Various polymer brushes with controlled molecular weight and narrow molecular weight distribution were grafted from the GO surface by surface-initiated atom transfer radical polymerization (SI-ATRP). The modification of GO with poly(n-butyl methacrylate) (PBMA), poly(glycidyl methacrylate) (PGMA), poly(trimethylsilyloxyethyl methacrylate) (PHEMATMS) and poly(methyl methacrylate) (PMMA) was confirmed by thermogravimetric analysis (TGA) coupled with online Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). Various grafting densities of GO-based materials were investigated, and conductivity was elucidated using a four-point probe method. Raman shift and XPS were used to confirm the reduction of surface properties of the GO particles during SI-ATRP. The contact angle measurements indicated the changes in the compatibility of GOs with silicone oil, depending on the structure of the grafted polymer chains. The compatibility of the GOs with poly(dimethylsiloxane) was also investigated using steady shear rheology. The tunability of the electrorheological, as well as the photo-actuation capability, was investigated. It was shown that in addition to the modification of conductivity, the dipole moment of the pendant groups of the grafted polymer chains also plays an important role in the electrorheological (ER) performance. The compatibility of the particles with the polymer matrix, and thus proper particles dispersibility, is the most important factor for the photo-actuation efficiency. The plasticizing effect of the GO-polymer hybrid filler also has a crucial impact on the matrix stiffness and thus the ability to reversibly respond to the external light stimulation.
Keywords: grafting; conductivity; compatibility; graphene oxide; smart composites; SI-ATRP